2019
DOI: 10.1007/s11427-018-9437-7
|View full text |Cite
|
Sign up to set email alerts
|

The lifestyle transition of Arthrobotrys oligospora is mediated by microRNA-like RNAs

Abstract: The lifestyle transition of fungi, defined as switching from taking organic material as nutrients to pathogens, is a fundamental phenomenon in nature. However, the mechanisms of such transition remain largely unknown. Here we show microRNA-like RNAs (milRNAs) play a key role in fungal lifestyle transition for the first time. We identified milRNAs by small RNA sequencing in Arthrobotrys oligospora, a known nematode-trapping fungus. Among them, 7 highly expressed milRNAs were confirmed by northern-blot analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…For example, a recent work has generated a strain lacking the signaling scaffold protein Soft and shown that cell-cell fusion is required for ring closure in Duddingtonia flagrans (40). In A. oligospora, ATCC24927-background trapping-deficient mutations have been isolated: adhesin protein Mad1 (41), autophagy protein Atg8 (42), mitogen-activated protein kinase Slt2 (43), pH sensor PalH (44), NADPH oxidase NoxA (45), low-affinity calcium uptake system proteins (46), Rab GTPase Rab7A (38), actin-associated protein Crn1 (47), Woronin body component Hex1 (48), malate synthase Mls (49), glycogen phosphorylase Gph1 (50), transcription factors VelB (51) and StuA (52), and microRNAprocessing protein Qde2 (53), to which we add the G-protein β-subunit Gpb1. However, a mechanistic view of how these and other molecular players are interconnected during the interaction of A. oligospora with their prey is totally lacking.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent work has generated a strain lacking the signaling scaffold protein Soft and shown that cell-cell fusion is required for ring closure in Duddingtonia flagrans (40). In A. oligospora, ATCC24927-background trapping-deficient mutations have been isolated: adhesin protein Mad1 (41), autophagy protein Atg8 (42), mitogen-activated protein kinase Slt2 (43), pH sensor PalH (44), NADPH oxidase NoxA (45), low-affinity calcium uptake system proteins (46), Rab GTPase Rab7A (38), actin-associated protein Crn1 (47), Woronin body component Hex1 (48), malate synthase Mls (49), glycogen phosphorylase Gph1 (50), transcription factors VelB (51) and StuA (52), and microRNAprocessing protein Qde2 (53), to which we add the G-protein β-subunit Gpb1. However, a mechanistic view of how these and other molecular players are interconnected during the interaction of A. oligospora with their prey is totally lacking.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent work has generated a strain lacking the signaling scaffold protein Soft and shown that cell-cell fusion is required for ring closure in Duddingtonia flagrans (41). In A. oligospora , ATCC24927-background trapping-deficient mutants have been isolated: adhesin protein Mad1 (42), autophagy protein Atg8 (43), mitogen-activated protein kinase Slt2 (44), pH sensor PalH (45), NADPH oxidase NoxA (46), low-affinity calcium uptake system proteins Fig1 and Fig2 (47), Rab GTPase Rab7A (48), actin-associated protein Crn1 (49), Woronin body component Hex1 (50), malate synthase Mls (51), glycogen phosphorylase Gph1 (52), transcription factors VelB (53) and StuA (54), and microRNA processing protein Qde2 (55), to which we add the G-protein β subunit Gpb1. However, a mechanistic view of how these and other molecular players are interconnected during the interaction of A. oligospora with their prey is totally lacking.…”
Section: Resultsmentioning
confidence: 99%
“…They can trap and digest nematodes using specialized trapping devices (traps), such as adhesive networks and knobs and constricting rings. The development of these traps is a key indicator of their switch from saprophytic to predacious lifestyles ( 19 21 ). Arthrobotrys oligospora is a representative species of NT fungi that produces adhesive networks to capture nematodes ( 21 ).…”
Section: Introductionmentioning
confidence: 99%